2022
DOI: 10.3390/en15031200
|View full text |Cite
|
Sign up to set email alerts
|

Application of Fourier Sine Transform to Carbon Nanotubes Suspended in Ethylene Glycol for the Enhancement of Heat Transfer

Abstract: There is no denying fact that nanoparticles of carbon nanotubes are employed to improve the performance of thermal stability in comparison with traditional nanoparticles, this is because nanoparticles of carbon nanotubes possess outstanding material properties. In this manuscript, a mathematical model of mixed convective flow based on carbon nanotubes suspended in ethylene glycol has been developed and derived by means of Fourier Sine transform. In order to analyze the thermophysical properties of nanofluid, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Natural convection has become an active research topic due to its lower cost and wide applications in engineering. Several models were developed for calculating the efficiency of thermal conductivity in solid and fluid systems [1][2][3][4][5][6]. In [7], Choi showed that adding some nano metal particles to the base fluid increases its conductivity.…”
Section: Ramentioning
confidence: 99%
“…Natural convection has become an active research topic due to its lower cost and wide applications in engineering. Several models were developed for calculating the efficiency of thermal conductivity in solid and fluid systems [1][2][3][4][5][6]. In [7], Choi showed that adding some nano metal particles to the base fluid increases its conductivity.…”
Section: Ramentioning
confidence: 99%
“…Mansour et al [ 2 ] examined how different models of nanofluid's properties affected the thermo-hydraulic behavior of pipe flow. Besides, applying Fourier sine transforms to find the exact solution of nanofluids' temperature and velocity profiles opened the door to groundbreaking research in the augmentation of heat transfer performance using nanofluids [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…In many cases, analytical or exact solutions are very difficult to investigate. Therefore, mathematicians have tried to develop and use several numerical techniques with fractional derivative and integral operators [23][24][25]. In this connection, in 2017, Li et al presented three efficient techniques, namely the finite difference method, the Galerkin finite element method, and the spectral method, for the solutions of some FPDEs [26].…”
Section: Introductionmentioning
confidence: 99%